The Development of Small and Medium Scale Enterprises (SME's) in East Java: A Shift-Share Analysis - Setyo Tri Wahyudi (e-2477-1929)
Disparities in economic growth across the region in East Java, especially regions in the North of East Java and the South of East Java is still quite striking. The fact shows that the Region in the North of East Java is still dominating in term of sectoral contribution compare to South Regions. This condition occurs due to a policy that only oriented on the development of industrial zones in the North regions, but not for the South. Meanwhile, the Small and Medium Scale Enterprises (SME's) in the South East Java shows growth rapidly. This study aims to identify the potential of Small and Medium Scale Enterprises (SME's) in the South Regions of East Java. Using sample of Regency/City level, the research methods are (i) mapping the potential sector using Location Quotient (LQ) and (ii) conduct a Shift Share analysis. The results showed that there are 9 of 17 sectors in Regency/City in East Java as the basis sector or has the potential to be developed. Meanwhile, the Shift Share analysis for both region shows that there is any shift in economic structure. Then, we can conclude that the emphasizing policy to encourage the development of SME’s will be able to drive the regional growth.Keywords: Small Medium Enterprises, Shift-Share analysis